-1 and 1
-2 and 2
-3 and 3
-4 and 4
-5 and 5
because when u subtract the numbers or add you will get 0
s = p + g/h for g.
Answer:
g = h(s-p)
Step-by-step explanation:
g = h(s -p)
Answer:
(s-p)*h =g
Step-by-step explanation:
s = p + g/h
Subtract p from each side
s-p = p=p + g/h
s-p = g/h
Multiply by h
(s-p) *h =g/h *h
(s-p)*h =g
Answer:
Step-by-step explanation:
we know that
The formula to calculate continuously compounded interest is equal to
where
A is the Final Investment Value
P is the Principal amount of money to be invested
r is the rate of interest in decimal
t is Number of Time Periods
e is the mathematical constant number
we have
substitute in the formula above
Answer
x=a 1/2+i / a 1/2
Step-by-step explanation: